Climate Change Impacts on the Patagonian Shelf Break Front - Franco, Barbara Cristie (2022)
We characterize long-term trends of sea surface temperature (SST), absolute dynamic topography, and chlorophyll-a (CHL) in the Patagonian shelf break front (SBF) using 27 years (1993–2019) of satellite data. Warming of the Argentinean shelf waters and the southwestward displacement of the Brazil-Malvinas Confluence (BMC) impact the northernmost extension of the SBF. Cooling of the Malvinas Current (MC) and the concurrent warming of the adjacent shelf waters lead to a significant increase of SST gradients along the outer shelf. The southwestward displacement of the BMC implies a similar shift of the SBF. An increase in CHL trend appears to be associated with southerly wind anomalies along the shelf break. We estimate a southward shift of the northernmost penetration of the MC of −0.11 ± 0.076°/decade.